The Implementation Of Semantic Mapping To Improve Students Vocabulary Mastery - Nur Fitriani; Nadirah Usman; Andi Asrifan; Tadjuddin posi; Sam hermansyah . (La Ogi : English Language Journal, 2022)
The objective of the research was to find out whether or not semantic mapping can improve the ability of the students of SMP Negeri 2 Kulo in vocabulary. This research employed the method of the research was pre experimental method design. The population was the second year students of SMP Negeri 2 Kuloin 2018-2019 academic years. Total number of population was 20 students and one class was taken as sample (VIII.1) by using clustersampling technique, total munber of sample was 20. The instrument used in this research was to vocabulary test. The result of this research showed that in pre-test the mean score (43.15) is lower than post-test (58.50). It proved that there was significant improvement of students’ vocabualry using semantic mapping. The result of the P-value (0.000) was lower than level of significant (alpha (α)=0.05). This means that H1 was accepted. The researcher concluded that teaching vocabulary mastery by using SEMANTIC MAPPING improved the students’ vocabulary mastery at SMP Negeri 2 Kulo.